2010
DOI: 10.1038/sc.2010.128
|View full text |Cite
|
Sign up to set email alerts
|

Device use, locomotor training and the presence of arm swing during treadmill walking after spinal cord injury

Abstract: Objectives Determine the presence of walking-related arm swing following spinal cord injury (SCI), associated factors, and whether arm swing may change following locomotor training (LT). Design Observational, cross-sectional study from a convenience sample with pre-test/post-test from a sample subset. Setting Malcom Randall VAMC and University of Florida, Gainesville, FL. Methods Arm movement was assessed during treadmill stepping, pre-LT, in 30 individuals with motor incomplete SCI (iSCI, American Spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…In conclusion, our findings corroborate the newly emerging observation that adult mammalian spinal cord contains inherent circuits that may be therapeutically recruited and modulated to restore function posttrauma (8,49,53,55). These results collectively suggest it is plausible that direct axonal connections from motor cortex neurons to spinal cord are not essential for reestablishment of basic locomotion after mammalian SCI (55)(56)(57).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In conclusion, our findings corroborate the newly emerging observation that adult mammalian spinal cord contains inherent circuits that may be therapeutically recruited and modulated to restore function posttrauma (8,49,53,55). These results collectively suggest it is plausible that direct axonal connections from motor cortex neurons to spinal cord are not essential for reestablishment of basic locomotion after mammalian SCI (55)(56)(57).…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, following thoracic lesion of descending motor pathways, neuroplasticity also occurs more caudally in the PSN network and lumbar CPG, a semiautonomous neural circuit for locomotion (45,49). Studies examining "spinalized" cats or humans with incomplete SCI have demonstrated that motor cues, such as weight-suspended treadmill training or treadmill walk, can reanimate the CPG and its reengagement of arm swing, respectively (52,53). Previously, a combinatorial application of direct electrical stimulation or administration of 5-HT receptor agonists enabled locomotion in spinalized rodents with dual spinal cord hemisections by igniting the PSN network for CPG activation through relaying CST signals (44).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only our group is investigating arm swing during walking post-iSCI. We recently described varied arm swing presentation during walking on a treadmill without assistive devices post-injury [17]. The current study furthers this characterization by describing arm and leg coordination.…”
Section: Introductionsupporting
confidence: 60%
“…Therefore, the 1:1, arm:leg frequency pattern used post-iSCI with slow CWSs may be a compensatory strategy to enhance balance. Experience post-iSCI [17], attributes other than spinal injury (e.g. age, height, weight) known to influence gait [25], and/or the testing environment, however, also should be given equal consideration as factors potentially influencing the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in human patients with an incomplete spinal cord injury with residual capacity to walk, some of the most visible changes in the locomotor pattern are a reduction in preferred walking speed, an inability to walk at fast speeds, and/or a decreased capacity to sustain walking at fast speeds (Pepin et al 2003a(Pepin et al , 2003b. Spinal cord-injured patients display poor interlimb coordination between the arms and legs, and the majority of patients do not move their arms during walking (Tester et al 2011(Tester et al , 2012. Impairments in interlimb coordination could be due to the slower walking speeds adopted by many spinal cord-injured patients, or the slower walking speeds could impair interlimb coordination.…”
Section: Functional Considerations and Concluding Remarksmentioning
confidence: 99%